Acceptability of emergency contraception in Brazil, Chile, and Mexico. 2 - Facilitating factors versus obstacles - Díaz Soledad; Hardy Ellen; Alvarado Gloria; Ezcurra Enrique (Cadernos de Saúde Pública, 2003)
A multi-center study was performed in Brazil, Chile, and Mexico to identify factors that may facilitate or hinder the introduction of emergency contraception (EC) as well as perceptions concerning emergency contraceptive pills. Background information on the socio-cultural, political, and legal context and the characteristics of reproductive health services was collected. The opinions of potential users and providers were obtained through discussion groups, and those of authorities and policymakers through semi-structured interviews. Barriers to introduction included: perception of EC as an abortifacient, opposition by the Catholic Church, limited recognition of sexual and reproductive rights, limited sex education, and insensitivity to gender issues. Facilitating factors were: perception of EC as a method that would prevent abortion and pregnancy among adolescents and rape victims; interest in the method shown by potential users as well as by some providers and authorities. It appears possible to reduce barriers through support from segments of society committed to improving sexual and reproductive health and adequate training of health care providers.